2023
DOI: 10.1038/s41598-023-30051-x
|View full text |Cite
|
Sign up to set email alerts
|

Deduction of the operable design space of RP-HPLC technique for the simultaneous estimation of metformin, pioglitazone, and glimepiride

Abstract: A reversed-phase RP-HPLC method was developed for the simultaneous determination of metformin hydrochloride (MET), pioglitazone (PIO), and glimepiride (GLM) in their combined dosage forms and spiked human plasma. Quality risk management principles for determining the critical method parameters (CMPs) and fractional factorial design were made to screen CMPs and subsequently, the Box–Behnken design was employed. The analytical Quality by Design (AQbD) paradigm was used to establish the method operable design reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Then, the risk assessment tool for the factors affecting the performance of the method is identified by studying the CMPs that influence CQAs. 50–52…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the risk assessment tool for the factors affecting the performance of the method is identified by studying the CMPs that influence CQAs. 50–52…”
Section: Resultsmentioning
confidence: 99%
“…Then, the risk assessment tool for the factors affecting the performance of the method is identied by studying the CMPs that inuence CQAs. [50][51][52] The HPLC process is inuenced by numerous factors, some of which must be discarded because they do not have a signicant impact. Risk assessment determined the selected (CQAs) in relation to several CMPs, which are represented in the Ishikawa diagram, as shown in Fig.…”
Section: Efficiency (Evg 1st Pillar)mentioning
confidence: 99%
“…Ultraviolet spectrophotometry [15][16][17][18][19][20][21], highperformance liquid chromatography (HPLC) [22][23][24][25][26][27][28][29][30], high-performance thin-layer chromatography (HPTLC) [31][32][33][34][35][36][37], liquid chromatography-mass spectrometry (LC-MS) [38][39][40][41][42][43][44], and gas chromatography-mass spectrometry (GC-MS) [45] are among the analytical approaches stated in the literature for quantifying the concentrations of LBZ and GLM separately or in blend with other substances, in bulk drug samples or pharmaceutical formulations. Only two analytical methods have been reported [22,23] for determining LBZ individually, and these methods cannot be used to estimate the drugs in combined formulations.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the existing literature focusing on the quantitative analysis of TGT and PGZ indicated that efforts have been directed toward devising analytical methods for these individual drugs, as well as in combination with other medications. These efforts have resulted in developing various methods including UV spectroscopy [3,[12][13][14][15], HPLC [2,3,7,[16][17][18][19][20][21][22][23], high-performance thin-layer chromatography (HPTLC) [15,[24][25][26][27][28][29], and LC-MS [23,[30][31][32][33][34][35][36]. Among the various methods that have been reported, the work by Gheewala et al in 2017 provided a comprehensive account of simultaneously determining TGT and PGZ within a synthetic mixture using both UV spectroscopy and HPLC.…”
Section: Introductionmentioning
confidence: 99%